2010
DOI: 10.1021/om900836b
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of the [2+2+2] Cyclotrimerization of Acetylene Catalyzed by Wilkinson’s Catalyst, RhCl(PPh3)3

Abstract: In this work we report density functional calculations at the B3LYP level of the [2þ2þ2] intermolecular cyclotrimerization of three acetylene molecules catalyzed by Wilkinson's catalyst. This process corresponds to the simplest [2þ2þ2] cyclotrimerization reaction. The results obtained show that this reaction is thermodynamically very favorable and that the rate-determining step is the initial oxidative coupling between two acetylene molecules with a relatively low Gibbs free energy barrier of 19.8 kcal 3 mol -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 54 publications
4
46
0
Order By: Relevance
“…The simplicity of the 1 H and 13 C NMR spectra proved a symmetrical structure due to the presence of a C 2 axis. The anti disposition of the new CH c À CH c' centres was established by taking into account the trans configuration of the original double bond in the starting compounds 1 and 2, respectively, and the NOE data.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The simplicity of the 1 H and 13 C NMR spectra proved a symmetrical structure due to the presence of a C 2 axis. The anti disposition of the new CH c À CH c' centres was established by taking into account the trans configuration of the original double bond in the starting compounds 1 and 2, respectively, and the NOE data.…”
Section: Resultsmentioning
confidence: 87%
“…Aquests endiins shan emprat com a substrats en processos de cicloaddició [2+2+2] catalitzats pel To reduce the computational effort required, the tosyl moieties present in the experimental enediynes and the three phenyl groups of the Wilkinson catalyst were substituted by hydrogen atoms. [13,14] A previous study [15] with macrocyclic systems revealed that the substitution of the tosyl groups by hydrogen atoms reduces the exothermicity of the [2+2+2] cycloaddition by about 10 %. Although this quantity is not negligible, we expect it to have only a slight effect on the different reaction mecha- nisms studied here and therefore the conclusions reached by our model systems will still be valid for experimental systems.…”
mentioning
confidence: 99%
See 3 more Smart Citations